(untitled) (Edad Media. Revista de Historia, 2020)
This essay examines the impact of tax pressure due to war on the rural communities of the Crown of Aragon. It focuses on a case study based on notarial sources and centered on north-eastern Catalonia during the War of the Two Peters (1356-1366). After presenting the features of the area under investigation, it describes how the subsidies granted in the assembly of the estates with the king implied the whole of the territory with an unprecedented degree. It analyses the types of instruments and the profile of creditors of series of credit operations by several places of the diocese of Girona between the years 1364 and 1367 connected with the aforementioned tax contributions. Beyond the undeniable weight of urban capitals, the role of some countrymen and peasants is also important. It concludes with an approach on the effects all these dynamics may have on the communities not only from an institutional viewpoint, but also with regard to their socioeconomic composition.